Youth Interfaith Dialogue in Everyday Citizenship in Indonesia: Bridging Religious Diversity and Citizenship Challenges - Kusmayani, Anisa Eka Putri (FOCUS, 2023)
This research explores the role of interfaith dialogue among Indonesian youth in fostering everyday citizenship, particularly within the context of religious diversity. The study draws on the dynamics of interfaith engagement, emphasizing its significance in promoting social cohesion, peace, and civic participation. The framework integrates the "Seven Moments of Inter-religious Dialogue" proposed by J.B. Banawiratma and Stokke's (2017) dimensions of citizenship, including membership, legal status, rights, and participation. Examining the Abrahamic religions context, the research delves into historical challenges and the potential for dialogue to overcome intergenerational religious biases. The study highlights the necessity of understanding religious pluralism and building bridges among communities, particularly within the Muslim-Christian-Jewish framework. In the Indonesian youth context, the research identifies various interfaith dialogue initiatives undertaken by youth organizations across regions. It explores how these initiatives contribute to societal harmony, reduce radicalization, and empower civil society. The research also addresses challenges such as power dynamics and leadership influence in maintaining peace, emphasizing the grassroots' role. Moving beyond religious discourse, the study analyzes the intersection of interfaith dialogue with everyday citizenship issues in Indonesia. It investigates how dialogue addresses challenges related to LGBTQ+ rights, indigenous religious rights, and interreligious marriage. The research argues that interfaith dialogue plays a pivotal role in acknowledging inclusive citizenship, facilitating coexistence, and addressing complex societal issues. The findings suggest that interfaith dialogue not only promotes religious understanding but also enhances civic engagement, contributing to social justice and peace. The research concludes with insights into the potential of interfaith dialogue to bridge gaps between diverse religious and non-religious perspectives, fostering a more inclusive and tolerant citizenship in Indonesia.